2003
DOI: 10.1116/1.1597889
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of MeV ion beams by means of tapered glass capillary optics

Abstract: We present evidence of the focusing effects of fine glass capillary optics for MeV He ion beams. The glass capillary optics are formed by a puller as to have inlet diameters of about 1 mm and outlet diameters of submicrons. The total length of the optics is about 50 mm. Impingent MeV ions to such optics are reflected by the inner wall several times, in a very similar process to the so-called surface channeling. The majority of incident ions are lost by the dechanneling, or large-angle scattering process, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
42
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(45 citation statements)
references
References 5 publications
1
42
0
2
Order By: Relevance
“…A similar glass capillary was used to transport proton or He ion beam in a MeV region. 9 In this case, however, the beam touches the inner wall and suffers small angle scattering with the wall surface during the transport.…”
mentioning
confidence: 99%
“…A similar glass capillary was used to transport proton or He ion beam in a MeV region. 9 In this case, however, the beam touches the inner wall and suffers small angle scattering with the wall surface during the transport.…”
mentioning
confidence: 99%
“…To overcome such technical but serious problems, we have developed a scheme using a tapered glass capillary with a thin window at its outlet. 12,13 This scheme can realize pinpoint energy deposition and three-dimensional selection of the bombarding point by observing the outlet through a microscope with a precision of a micron or better in an arbitrary position of a living cell or in any liquid object. Figure 1͑a͒ shows a drawing of the microbeam preparation setup installed on an X-Y stage, which is aligned by the upstream micrometers with respect to the beam line.…”
mentioning
confidence: 99%
“…1͑b͔͒ with inlet and outlet diameters of 0.8 mm and several micrometers, respectively. 12,13 The downstream micrometers are used to align the capillary to the beam axis with a step of 0.5 mrad. The capillary outlet is placed in the focus of an optical microscope, which is installed on a three-dimensional stage.…”
mentioning
confidence: 99%
“…Recently, many studies have been reported on microbeam production of keV-MeV accelerated ions using tapered glass capillaries [1][2][3]. Microbeams by the capillaries have advantages of low cost, easily positioning on the target and preferable sizes of beams.…”
Section: Introductionmentioning
confidence: 99%